2019
DOI: 10.1186/s13287-019-1290-1
|View full text |Cite
|
Sign up to set email alerts
|

Fat extract improves fat graft survival via proangiogenic, anti-apoptotic and pro-proliferative activities

Abstract: Background: Our previous study proved that nanofat could enhance fat graft survival by promoting neovascularization. Fat extract (FE), a cell-free component derived from nanofat, also possesses proangiogenic activity. Objectives: The aim of this study was to investigate whether FE could improve fat graft survival and whether FE and nanofat could work synergistically to promote fat graft survival. The underlying mechanism was also investigated. Methods: In the first animal study, human macrofat from lipoaspirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 33 publications
(40 reference statements)
5
53
0
Order By: Relevance
“…CEFFE contains about 59 proteins related to angiogenesis, including VEGF and EGF [25]. It attenuates ischemic injury in a mouse hindlimb ischemic model [25] and improves fat graft [35] and skin flap [36] survival by accelerating blood vessel formation. In the current study, we confirmed that CEFFE promoted angiogenesis during tissue expansion (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…CEFFE contains about 59 proteins related to angiogenesis, including VEGF and EGF [25]. It attenuates ischemic injury in a mouse hindlimb ischemic model [25] and improves fat graft [35] and skin flap [36] survival by accelerating blood vessel formation. In the current study, we confirmed that CEFFE promoted angiogenesis during tissue expansion (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We used immunohistologic staining for histological evaluation. Studies have shown that vascularisation is crucial for fat survival and repassage [ 22 ]. So we measured capillary density within the grafts via immunohistochemical (IHC) staining of anti-CD34 antibody in tissue sections to evaluate the effect of hADMSC-sEVs on neoangiogenesis of grafted fat.…”
Section: Resultsmentioning
confidence: 99%
“…ADSC composes minor fraction in the graft, but their potential for regeneration is greater than mature adipocytes. Studies of which ADSC or SVF is added to enhance fat graft survival suggest that progenitor cells elicit crucial role in cell proliferation as well as angiogenesis and anti‐apoptosis 18‐21 . Therefore, our study focused on the survival and function of ADSC in the cryopreserved lipoaspirate.…”
Section: Discussionmentioning
confidence: 99%